Acceptability, safety and perceived impact of providing a fact sheet to young people about cognitive symptoms in depression. Issue 2 (11th February 2020) - Bryce, Shayden; Cooke, Melanie; Yuen, Hok Pan; Allott, Kelly
Abstract: Aim: Cognitive deficits are common in young people, aged 15‐25, with depression. Nevertheless, these symptoms are not routinely addressed in clinical care. This study examined the acceptability, safety, and reported impact on cognitive knowledge and strategy use, of a newly developed fact sheet ( Thinking about Thinking Skills in Depression ) for young people with depression. Method: Twenty‐three participants, aged 15‐25 years old ( M = 19.6, SD = 3.2), receiving community‐based treatment for a depressive disorder were delivered the fact sheet by their case manager and completed pre‐ and post‐assessments conducted 3 weeks apart. Primary outcomes included: acceptability, safety, subjective distress, knowledge of cognition and use of, and confidence in using, cognitive strategies. Exploratory outcomes included depression symptoms, perceived cognitive difficulties, self‐efficacy and self‐esteem. Case manager perspectives were obtained using an anonymous online survey. Results: Participant experiences of the fact sheet were favourable. Most reported that the amount of content provided was appropriate (91%), looked at the fact sheet again after receiving it (83%), and tried at least one strategy (57%). Participants reported significant improvements in their knowledge of cognitive difficulties and a greater use of, and confidence in using, cognitive strategies. Distress did not change following fact sheet delivery, supporting safety. Perceived improvements in depression symptoms and cognitive deficits, but not self‐esteem or self‐efficacy, were revealed. Case manager perspectives were also positive. Conclusion: Written fact sheet resources are an acceptable, safe and pragmatic method of delivering information about cognitive difficulties to young people with depression.